Pengaruh Penggunaan Dompet Digital GoPay Terhadap Perilaku Konsumtif Mahasiswa Politeknik Negeri Bandung - Maharani, Putri Regina (Asosiasi Ahli Administrasi Indonesia, 2023)
The purpose of this study was to determine the effect of the use of digital wallets on the consumer behavior of students. This study was conducted at the Bandung State Polytechnic (Polban with a total of 110 respondents from engineering and non-engineering majors, both who have or are still using the GoPay digital wallet. This study used descriptive analysis, validity test, reliability test, correlation test, and simple regression. Data collection techniques through questionnaires with the media in the form of Google Forms that are distributed through social media and directly to respondents who meet the criteria. Based on the results of the research, it was obtained that 16.7% of consumptive behavior was influenced by the use of GoPay digital wallets, while 83.3% of consumptive behavior was influenced by other variables that were not discussed in this study. The results of this study show that the influence of the use of GoPay digital wallet on the consumptive behavior of Polban students is relatively low.